Language lateralization in a patient with temporal lobe epilepsy and callosal agenesis - Alsaadi, Taoufik (Epilepsy Behav Case Rep, 2014)
The corpus callosum has been proposed as a mechanism of interhemispheric inhibition that allows language dominance to develop [1]. Callosal agenesis or dysgenesis provides a test of this hypothesis, as patients lacking a normal corpus callosum should also lack normal language lateralization [2]. We report pre- and postoperative functional magnetic resonance imaging (fMRI) and neuropsychological testing in a patient with partial callosal agenesis who underwent a right temporal lobectomy for medically refractory seizures.